The midwife's labour and birth handbook - Chapman, Vicky (Wiley-Blackwell, 2013)
"This fully revised and updated third edition of The Midwife's Labour and Birth Handbook is a practical and accessible guide to midwifery care. It addresses important questions such as: Why are women being pressured into caesarean section for breech presentation when the evidence is equivocal? If a baby needs assisted ventilation breaths at birth, why not bring the ambubag to the baby and leave the cord intact so the baby can benefit from the extra maternal oxygen supply? Why is skin-to-skin contact at birth so rarely offered to preterm babies when there is evidence of benefit? This well-regarded text promotes normality and woman-centred care, using research, evidence-based guidelines and anecdotal accounts from women. It challenges practice and guidelines which are biased or based on poor evidence. Guidance is offered on how to deal with difficult, sometimes controversial, situations."--The publisher.